2021
DOI: 10.4103/ijdvl.ijdvl_573_18
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus superinfection over untreated candidiasis resulting in oronasal fistula

Abstract: with history of wound in mouth, causing nasal regurgitation of food for a period of 4 weeks. Examination revealed, a 3 × 3 cm oval ulcer at the junction of hard and soft palate in the midline, covered with extensive pseudomembrane and associated with foul smell. The ulcer was tender, with well-defined borders and everted margins [Figure 1]. Occlusal radiographs showed evidence of communication with the nasal cavity. Routine blood investigations along with serology (VDRL for syphilis and ELISA for HIV) were neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sadhu et al have reported that postoperative infection caused poor palatal wound healing, especially in adults ( Sadhu, 2009 ). A methicillin-resistant Staphylococcus aureus infection with untreated candidiasis leading to poor palatal wound healing has also been reported ( Palla et al, 2019 ). Unfortunately, the studies did not release the relationship between these infections and poor palatal wound healing in detail.…”
Section: Aspects Of Studiesmentioning
confidence: 99%
“…Sadhu et al have reported that postoperative infection caused poor palatal wound healing, especially in adults ( Sadhu, 2009 ). A methicillin-resistant Staphylococcus aureus infection with untreated candidiasis leading to poor palatal wound healing has also been reported ( Palla et al, 2019 ). Unfortunately, the studies did not release the relationship between these infections and poor palatal wound healing in detail.…”
Section: Aspects Of Studiesmentioning
confidence: 99%